Supporting development of community-based tourism: A perspective from "Sewu Kembang" Nglurah tourism village in Karanganyar regency - Henny Kustini; Ratna Susanti (Journal of Advanced Multidisciplinary Research, 2020)
In Nglurah tourism village, it can be found some attractions that have the potential to develop. Some attractions have been developed by involving the community in its management, but its development has not been as expected. The purpose of this research is to know the attitude of the community and the level of human resources of the community of Nglurah tourism village in supporting the development of community-based tourism and the right strategy for its development. The CBT concept (Community-Based Tourism) that is applied to achieve sustainable tourism management was applied in the forms of local community participation, tourism village institute creation, environmental-based tourism attractions management, and the creation of small business activities by the locals. This research uses a qualitative approach with a descriptive type of research. The data resource of this research was in the forms of primary and secondary data with a data collection that was done through observation, interviews, documentation, and FGD (Focus Group Discussion). The data analysis uses stages, which are data collection, data condensation, data presentation, and conclusion drawing. The result of this research shows that the management of tourist attraction in "Sewu Kembang" Nglurah Tourism Village appears from the initiative of the local's people, the locals have agreed on the creation of tourism village institute, the creation of Pleseran Campsite, Dukutan ceremonies, Embankment site management priority programs as the main attraction and the emergence of community business activities as a result of the tourism attraction management.